Internet of Things-enabled technologies for weight management in children and adolescents: Protocol for a systematic review - Lam, C; Milne-Ives, M; Van Velthoven, M; Meinert, E (JMIR Publications, 2020)
Background: Childhood obesity is a serious global issue, leading to increased medical spending on obesity-related diseases such as cardiovascular diseases and diabetes. There is a need for health care services that link health behavior to risk factors, such as diet and physical activity, and that provide better advice and feedback to users, which Internet of Things–enabled technologies could facilitate.